2012
DOI: 10.1074/jbc.m112.366476
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Signaling Inhibits Megakaryocytic Differentiation by Targeting Transcription Factor 3 (E2A) Cyclin-dependent Kinase Inhibitor 1A (CDKN1A) Transcriptional Axis

Abstract: Background: Cyclic AMP signaling impairs megakaryopoiesis through an unknown mechanism. Results: cAMP transcriptionally represses the transcription factor E2A with resultant impairment in the expression of its target CDKN1A. Conclusion: In discovering a mechanism for cAMP-induced inhibition, E2A is identified clearly as critical megakaryocytic factor. Significance: Elucidating the repertoire of necessary transcription factors is crucial for understanding control of megakaryocytic lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
7
1
Order By: Relevance
“…It has been recently reported that anagrelide inhibits megakaryopoiesis through its PDEIII inhibitory activity, by stimulating cAMP/PKA signaling and subsequently targeting the transcription factor E2A (TCF3), down-regulating its mRNA levels [25]. Nevertheless, both our microarray dataset and our Q-PCR analysis showed no evidence that anagrelide reduced TCF3 mRNA levels at the concentration tested.…”
Section: Discussioncontrasting
confidence: 72%
“…It has been recently reported that anagrelide inhibits megakaryopoiesis through its PDEIII inhibitory activity, by stimulating cAMP/PKA signaling and subsequently targeting the transcription factor E2A (TCF3), down-regulating its mRNA levels [25]. Nevertheless, both our microarray dataset and our Q-PCR analysis showed no evidence that anagrelide reduced TCF3 mRNA levels at the concentration tested.…”
Section: Discussioncontrasting
confidence: 72%
“…Neither 100 gM PKI nor 500 lM Rp-cAMP were able to revert anagrelide-induced inhibition of megakaryocyte maturation (Fig. 4A), while 100 gM PKI was able to partially revert the effect of 20 lM db-cAMP (data not shown), in accordance with recent data showing that cAMP exerts its inhibitory effect on the megakaryocyte lineage through a PKA-dependent mechanism [13]. Similar results were obtained when the addition of 500 gM anagrelide was delayed until day 4 of culture and also when lower 250 gM anagrelide concentrations or higher PKI doses, up to 1 lM, were used (data not shown).…”
Section: Role Of Camp Blockade In Anagrelide-induced Inhibition Of Mesupporting
confidence: 90%
“…found under these conditions (data not shown), whereas 500 gM anagrelide has been reported to repress the E2A/ p21 loop when added from the beginning of culture [13].…”
Section: Gene Expression Pattern Of Molecules Involved In Proplateletmentioning
confidence: 76%
See 1 more Smart Citation
“…Production of lentiviral particles by transient cotransfections of HEK293T cells was carried out using the calcium phosphate method, as previously described (59). Spinoculation of cells, puromycin selection of transduced CD34 + cells, and analysis of GFP + transduced primary progenitors were performed as previously described (59,60).…”
Section: Methodsmentioning
confidence: 99%